Spectroscopy of 22Mg relevant to explosive nucleosynthesis in classical novae and X-ray bursts - Brummer, Johann Wiggert (Stellenbosch : Stellenbosch University., 2020)
Thesis (PhD)--Stellenbosch University, 2020.